2015
DOI: 10.1139/cjz-2014-0265
|View full text |Cite
|
Sign up to set email alerts
|

Is erythrocyte size a strategy to avoid hypoxia in Wiegmann’s Torquate Lizards (Sceloporus torquatus)? Field evidence

Abstract: Is erythrocyte size a strategy to avoid hypoxia in Sceloporus torquatus? Field evidence 4 5 Abstract 6 This study examined changes of some different hematological parameters in a reptilian model 7 naturally exposed to altitude-associated hypoxia. Four populations of the Mexican lizard Sceloporus 8 torquatus (Wiegmann 1828) from different altitudes were sampled to evaluate erythrocyte count 9 (Erc), hematocrit (Hct), mean corpuscular hemoglobin concentration (MCHC) and erythrocyte size 10 (Ers). Blood was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
1
14
1
5
Order By: Relevance
“…Two important parameters related to blood-oxygen capacity-hematocrit and hemoglobin concentration-were correlated and increased within the first 3 wk of the experiment (increases of 12% and 4%, respectively). This response is concordant with numerous studies demonstrating that lizards from high-altitude populations have higher hemoglobin concentration and hematocrit compared to lowland populations (Vinegar and Hillyard 1972;Weathers and White 1972;Newlin and Ballinger 1976;González-Morales et al 2015;Lu et al 2015). Lowland lizards acclimated to simulated high-altitude hypoxia increased hemoglobin concentration and hematocrit and changed other parameters related to oxygen transport and use, but these responses were not identical to those in lizards native to highaltitude populations (Weathers and McGrath 1972;He et al 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Two important parameters related to blood-oxygen capacity-hematocrit and hemoglobin concentration-were correlated and increased within the first 3 wk of the experiment (increases of 12% and 4%, respectively). This response is concordant with numerous studies demonstrating that lizards from high-altitude populations have higher hemoglobin concentration and hematocrit compared to lowland populations (Vinegar and Hillyard 1972;Weathers and White 1972;Newlin and Ballinger 1976;González-Morales et al 2015;Lu et al 2015). Lowland lizards acclimated to simulated high-altitude hypoxia increased hemoglobin concentration and hematocrit and changed other parameters related to oxygen transport and use, but these responses were not identical to those in lizards native to highaltitude populations (Weathers and McGrath 1972;He et al 2013).…”
Section: Discussionsupporting
confidence: 90%
“…For lactate values, we found higher levels than reported by González-Morales et al (2015) in Sceloporus torquatus , González-Morales et al (2017) in S. grammicus , and Lewbart et al (2015) for marine iguanas ( Amblyrhynchus cristatus) . Very few studies have reported lactate levels in squamate reptiles ( Lewbart et al , 2015 ; González-Morales et al , 2015 , 2017 ), and most evaluated lactate production after exercise in diving reptiles ( Bartholomew et al , 1976 ; Seymour, 1979 ; Harms et al , 2003 ; Warren and Jackson, 2008 ). In squamates, blood lactate levels may be affected by altitude ( González-Morales et al , 2015 , 2017 ), exercise ( Bennett et al , 1981 ; Gleeson and Dalessio, 1989 ; Schuett and Grober, 2000 ) and handling ( Lewbart et al , 2015 ).…”
Section: Discussioncontrasting
confidence: 49%
“…Very few studies have reported lactate levels in squamate reptiles ( Lewbart et al , 2015 ; González-Morales et al , 2015 , 2017 ), and most evaluated lactate production after exercise in diving reptiles ( Bartholomew et al , 1976 ; Seymour, 1979 ; Harms et al , 2003 ; Warren and Jackson, 2008 ). In squamates, blood lactate levels may be affected by altitude ( González-Morales et al , 2015 , 2017 ), exercise ( Bennett et al , 1981 ; Gleeson and Dalessio, 1989 ; Schuett and Grober, 2000 ) and handling ( Lewbart et al , 2015 ). Lactate levels may also be influenced by glucose and oxygen levels ( Gleeson and Dalessio, 1989 ; Bennett, 1973 ), but apparently there is little dependence on body temperature ( Bennett and Litch, 1972 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2013; Gonzáles‐Morales et al . 2015), resulting in a higher affinity for oxygen. Individuals can exhibit changes in these variables within weeks (Gangloff et al .…”
Section: Discussionmentioning
confidence: 99%